Patterns of inflammation and immune activation by coreceptor use in people living with HIV-1 - Guerra-Castillo, Francisco Xavier; Pinto-Cardoso, Sandra; Ávila-Ríos, Santiago; Chávez-Torres, Monserrat; Peralta-Prado, Amy; González-Torres, Carolina; Gaytán-Cervantes, Javier; Requena-Benitez, Brenda; Díaz-Rivera, Dafne; Alaez-Verson, Carmen; Hernández-García, María Concepción; Bekker-Méndez, Vilma Carolina (Frontiers in Immunology, 2025)
IntroductionHuman immunodeficiency virus type 1 (HIV-1) utilizes either the CCR5 (R5) or CXCR4 (X4) coreceptor for host cell entry. Coreceptor switching from R5 to X4 and elevated immune activation have been associated with disease progression. X4-tropic HIV-1 is predominantly observed in the late stage of infection, when the immune environment characterized by chronic activation is optimal for their replication. The aim of this study was to determine viral tropism in late HIV presenters and who have not previously received treatment in Mexico City and its relationship with markers of chronic immune activation.MethodsA cross-sectional study was conducted on 122 people living with HIV (PLWH) recruited from two public health services. Viral tropism was determined using next-generation sequencing (NGS) and the geno2pheno algorithm. Immune activation was assessed through flow cytometry (CD38+, HLA-DR+), and soluble markers (sCD14, sCD163, IL-6) were quantified using enzyme-linked immunosorbent assays (ELISA). Differences in immune activation patterns between R5 and X4 group were explored using Mann-Whitney Wilcoxon test and t-test, and a principal component analysis (PCA). Logistic regression was used to evaluate associations between immune activation profiles and the presence of X4-tropic viruses.ResultsNinety-eight individuals had high-quality V3 loop sequences, 81.6% harbored only R5 variants (R5 group), while 18.4% had mixed R5/X4 populations (X4 group). Most PLWH had CD4+ T cell counts below 200 cells/µL, showing no significant difference between groups. Elevated levels of IL-6 were significantly associated with the R5 group (p = 0.01), while the X4 group showed increased expression of CD38+ and HLA-DR+CD38+ markers, although not statistically significant. Furthermore, IL-6 emerges as a negative predictor for the presence of X4 viruses (OR = 0.06, p = 0.006).ConclusionR5-tropic viruses are associated with elevated inflammatory responses in early stages, as indicated by higher IL-6 levels, while X4-tropic viruses may contribute to CD4+ T cell depletion through immune activation. Consequently, elevated levels of IL-6 emerge as a negative predictor for the presence of X4 viruses. The relationship between viral tropism and chronic immune activation in HIV-1 infection reflects a complex interplay which appears to be bidirectional.